Strengthening Product Identity and Packaging Design as an Effort to Empower the Home-Based Industry Toya Kumkuman (Ukupan) Radhika - Dharmendra, I Komang; I Made Agus Wirahadi Putra; Fathur Mahida Rangga; Yohanes Priyo Atmojo; Dinda Sari (Edumedia Solution, 2025)
The Toya Kumkuman (Ukupan) Radhika household industry, producing sacred water used in Balinese Hindu rituals, faces several challenges in its production and marketing. Despite positive market reception, the products were hindered by weak packaging quality, leakage due to manual sealing, and the absence of a clear brand identity. The lack of labels not only complicated consumer recognition but also prevented the inclusion of important information such as production and expiration dates, reducing competitiveness in the market. To address these issues, the community engagement team from ITB STIKOM Bali implemented a series of structured interventions. The activities included socialization with partners, mentoring on improved packaging design, the creation of product logos and labels reflecting the business philosophy, and the provision of production equipment such as a cup sealer and thermal printer. These implementations were complemented by workshops and training to ensure sustainable application. The outcomes demonstrated significant improvements: the new cup-sealed packaging reduced leakage and extended product shelf life, while the professionally designed logo and label strengthened product identity and consumer trust. Furthermore, the use of appropriate equipment enhanced efficiency in production and branding capacity. Overall, the program successfully empowered the partner by elevating product quality, improving market competitiveness, and fostering brand awareness, thereby ensuring the sustainability of Toya Kumkuman Radhika as a home-based industry. Industri rumahan Toya Kumkuman (Ukupan) Radhika yang memproduksi air suci untuk keperluan ritual umat Hindu di Bali menghadapi beberapa tantangan dalam proses produksi dan pemasaran. Meskipun mendapat sambutan positif dari masyarakat, produk ini masih terkendala oleh kualitas kemasan yang kurang baik, potensi kebocoran akibat penyegelan manual, serta ketiadaan identitas merek yang jelas. Tidak adanya label produk tidak hanya menyulitkan konsumen dalam mengenali produk, tetapi juga menghalangi pencantuman informasi penting seperti tanggal produksi dan kedaluwarsa, sehingga mengurangi daya saing di pasar. Untuk mengatasi masalah tersebut, tim pengabdian masyarakat dari ITB STIKOM Bali melaksanakan serangkaian kegiatan terstruktur. Kegiatan meliputi sosialisasi dengan mitra, pendampingan pengembangan desain kemasan, pembuatan logo dan label produk yang sesuai filosofi usaha, serta pemberian peralatan produksi seperti cup sealer dan printer thermal. Implementasi ini dilengkapi dengan pelatihan agar mitra mampu menerapkannya secara berkelanjutan. Hasil kegiatan menunjukkan adanya peningkatan signifikan: kemasan baru dengan segel cup mengurangi kebocoran dan memperpanjang daya simpan produk, sementara logo dan label profesional memperkuat identitas produk dan kepercayaan konsumen. Selain itu, penggunaan peralatan baru meningkatkan efisiensi produksi dan kapasitas branding mitra. Secara keseluruhan, program ini berhasil memberdayakan mitra dengan meningkatkan kualitas produk, memperkuat daya saing di pasar, serta membangun kesadaran merek sehingga mendukung keberlanjutan industri rumahan Toya Kumkuman Radhika